Coronary artery perforation during percutaneous intervention: incidence and outcome. Issue 5 (1st November 2002) - Gunning, M G; Williams, I L; Jewitt, D E; Shah, A M; Wainwright, R J; Thomas, M R
Abstract : Objective: To examine the clinical outcome of percutaneous coronary intervention where the procedure was complicated by vessel perforation. Setting: Tertiary referral centre. Methods: The procedural records of 6245 patients undergoing coronary intervention were reviewed. In 52 patients (0.8%) the procedure was complicated by vessel perforation, ranging from wire exit to free flow of contrast into the pericardial space. The majority of lesions treated were complex (37% type B, 59% type C) and 9 of 52 (17%) were chronic occlusions. Ten patients (19%) received abciximab. Four underwent rotational atherectomy (8%). Results: In 28 of 52 patients (54%) the perforation was benign and managed conservatively without the development of haemodynamically significant sequelae. In 24 of 52 (46%) a significant pericardial effusion ensued requiring drainage. Of these 24 procedures 6 had involved the treatment of a chronic occlusion (25%). Eight of the 24 patients were referred for emergency bypass surgery (33%), 3 of whom died. Of the remaining 16 not referred for surgery, 3 died. Of the 10 procedures complicated by vessel perforation where abciximab had been administered, 9 (90%) led to pericardial tamponade. Latterly 2 vessel perforations were successfully treated by the deployment of a covered stent. Conclusions: Coronary artery perforation with sequelae during intervention is rare—26 of 6245 (0.4%). This complication was seen in the treatment of chronic occlusions, which are therefore not risk-free procedures. The development of pericardial tamponade carries a high mortality. While prompt surgical intervention may be life saving, expertise in the use of covered stents may provide a valuable rescue option for this serious complication. Caution should be exercised where coronary perforation occurs and abciximab has been used.